Konsep Tasawuf Substantif Dalam Muhammadiyah - Masrur, Imam (Prodi Tasawuf dan Psikoterapi Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2019)
This research is exploring Islamic Sufism concept of the Muhammadiyah Organization. Formally,Muhammadiyah refuses classical sufism like Naqsabandiyah, Qadiriyah and etc. According to Muhammadiyah, sufism is often deviated into a tarekat by strict ritual practices, self isolated, and being unmindful people.Thisview motivates Muhammadiyah to make another concept of sufism accordingto Islam. The result explains that achieving spiritual grace are by reciting holy Quran, doing more sholat sunnah, zikir, fasting, and etc that in Islamics role. Muhammadiyah practices sufism in pure religious service and non-pure religious service according to Quran and hadist; it is called by substantive sufism. Sufism meant sincere, patient, tawakkal based on Prophets guide and only Allah. It is also meant as a balancing of material and spiritual, worldly and eschatological matters that based on Al-Quran and Sunnah. It is alsodenySufism that oriented with khalwat and reject the world. Another, the important of Muhammadiyahs attitudeÂ are faithful, doing religious service obediently, and being good human in environment. This is the sufism orientation that is not related with negative view like isolated, doing unusual, having faith by speculation and isolated from environment.